1986
DOI: 10.1002/jcu.1870140206
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of blood clot echogenicity

Abstract: The ability of B-mode ultrasound to follow effectively blood clot echogenicity changes over time under conditions of red cell preservation and lysis was evaluated. Blood clots were produced in cellulose dialysis tubing and then placed into appropriate baths of either saline or water. The echogenicity changes were then followed quantitatively using A-mode and qualitatively using B-mode imaging. Blood clots in saline showed an initial decrease followed by a leveling off in echogenicity. Blood clots in water show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Although ultrasound and venography are excellent instruments to diagnose DVT, they are apparently insufficient for the diagnosis of VCA [25][26][27][28]. In our patient, VCA could be detected by MRI after the diagnosis of the bilateral DVT by ultrasound.…”
Section: Discussionmentioning
confidence: 60%
“…Although ultrasound and venography are excellent instruments to diagnose DVT, they are apparently insufficient for the diagnosis of VCA [25][26][27][28]. In our patient, VCA could be detected by MRI after the diagnosis of the bilateral DVT by ultrasound.…”
Section: Discussionmentioning
confidence: 60%
“…The echogenicity decline was observed at both 6 and 48 hours after clot formation. Peter et al 10 reported that blood clots in saline showed an initial decrease followed by a plateau in echogenicity, and that point occurred 3.5 hours after the clots were made. In another study in the rat, it was reported that there seems to be some decrease in echogenicity several days after clot formation, suggesting that thrombus lysis occurs 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Septations within the hematoma have been reported in a horse' and in dogs.6 Splenic hematomas are anechoic, hypoechoic or hyperechoic to surrounding parenchyma, depending on how much time elapses between formation of the hematoma and ultrasonographic examination. 19,20 Based on in vitro studies performed on artificial blood clots, immediate echogenicity has been ascribed to red blood cells within a fibrin network, as neither plasma clots nor static packed red blood cells alone demonstrate echogenicity.20'21 Mere physical layering of red blood cells and fibrin seems adequate to generate an echo, as echogeniciEhas been demonstrated in static, unclotted blood, both in vitro and in vivo.21 Echogenicity of fresh blood clots remains constant for 24 hours, then decreases progressivelJbetween 24 and 48 hours.20 Both hemolysis of red blood cells within the clot2' and retraction of the clot" have been held responsible for this diminishing echogenicity . Nonuni-.form hemolysis is observed within artificial blood clots-' and is thought to account for the mixed echogenic pattern seen during aging of splenic hematomas.…”
Section: Discussionmentioning
confidence: 99%